Further Observations on the Comparative Efficacy of Some Indigenous Methods for the Protection of Underwater Timber Structures - M.V., Rao; C.J., Cherian; P.V., Cherian (Fishery Technology, 2025)
Results of long-term evaluation of several indigenous methods for protection of underwater timbers against wood boring organisms are reported in this paper. While unprotected control poles were totally destroyed due to severe infestation by the wood borers within a period of 9 months, the poles covered with copper-crome-arsenic (CCA)/ creosote fuel oil (CFA) treated coir rope lasted for 5 years, the ones studded with iron nails gave a life of 16 years and those plastered with cement over CCA treated coir rope winding/scattered nailing interconnected with winding wire were in sound condition even afterwards. Specific advantages offered by the methods in curtailing marine borer attack arc also mentioned.